Responsible Financial Consumption Behavior of Young Adults - Andrea LUČIĆ; Dajana BARBIĆ; Irena PALIĆ (Communications of International Proceedings, 2022)
Responsible financial consumption behavior depicts person’s self‐control in spending, planning for the future, seeking information, education, rational decision‐ making and solvency. As surveys of financial literacy indicate worryingly low levels of financial skills and knowledge among young adults, the purpose of this paper is to investigate responsible consumption behavior of young adults. Also, the paper investigates the influence of, attitudes and self-efficacy on the responsible financial consumption behavior of young adults. The quantitative research was conducted on the sample of 483 young adults using convenience sample of economics students. The results were analyzed by structural equation modeling, cluster and ANOVA analysis. The PLS-SEM model proved the influence of attitudes, and self-efficacy on responsible behavior. Also, the results indicate that more financially responsible young adults are less financed by allowance and more by scholarship and seek more information on money related issues in media, from friends and in banks when compared to the ones that are less financially responsible.
Keywords: Responsible Financial Consumption Behavior; Self-Efficacy; Attitudes; Young Adults